Способ получения N-замещенных имидов дифеновой кислоты - Яновский В. А. Вячеслав Александрович; Шардаков О. Н. Олег Николаевич; Яговкин А. Ю. Александр Юрьевич; Бакибаев А. А. Абдигали Абдиманапович
опубл. 20.10.06